157k views
2 votes
If f(x) = -4x2 - 6x-1 and g(x) = – x2 - 5x + 3, find (f+ g)(x).

User BradGreens
by
5.5k points

2 Answers

3 votes

Answer:

- 5x² - 11x + 2

Explanation:

(f + g)(x) = f(x) + g(x)

f(x) + g(x)

= - 4x² - 6x - 1 + (- x² - 5x + 3)

= - 4x² - 6x - 1 - x² - 5x + 3 ← collect like terms

= - 5x² - 11x + 2

User Glowka
by
5.2k points
3 votes

Answer:

-5x^2 -11x +2

Explanation:

f(x) = -4x^2 - 6x-1

g(x) = – x^2 - 5x + 3,

Add them together

f(x) = -4x^2 - 6x-1

+ g(x) = – x^2 - 5x + 3,

-----------------------------------

-5x^2 -11x +2

User Mistergreen
by
4.5k points